MIF -173 G > C (rs755622) Gene Polymorphism Modulates Tuberculosis Risk: Evidence from a Meta-analysis and Trial Sequential Analysis. Issue 1 (December 2017) - Areeshi, Mohammed; Mandal, Raju; Dar, Sajad; Jawed, Arshad; Wahid, Mohd; Lohani, Mohtashim; Panda, Aditya; Mishra, B.; Akhter, Naseem; Haque, Shafiul
Abstract The macrophage migration inhibitory factor (MIF) is a cytokine that plays an important role in inhibiting the growth of pathogenicMycobacterium tuberculosis (M.tb ) and regulates immune responses againstM.tb pathogen.MIF -173 G > C gene polymorphism may affect immunity in an individual and leads to susceptibility to tuberculosis (TB). A large number of studies have investigated the relevance of this polymorphism with TB risk, but their results were inconclusive. To obtain a precise conclusion, a meta-analysis was performed by retrieving six eligible studies from Google Scholar, PubMed (Medline), and EMBASE online databases. Overall combined analysis suggested increased TB risk betweenMIF -173 G > C polymorphism and overall risk in four genetic models, i.e., allelic (C vs. G: p = 0.001; OR = 1.517, 95% CI = 1.312 to 1.753), homozygous (CC vs. GG: p = 0.026; OR = 1.874, 95% CI = 1.079 to 3.257), heterozygous (GC vs. GG: p = 0.001; OR = 1.542, 95% CI = 1.273 to 1.868) and dominant model (CC + GC vs. GG: p = 0.001; OR = 1.631, 95% CI = 1.362 to 1.955). Similarly, increased TB risk was observed in subgroup analysis of Asian ethnicity. No publication bias was observed. These results suggested thatMIF -173 G > C variant is a significant risk factor for TB in overall and in Asian populations, and can be used as prognostic marker for TB susceptibility.